Evaluation of Complaint Handling by Guest Relation Officer at Zeus Restaurant, Apsara Beach Front Resort and Villa - Aulia, Natalia (Economy, Business, Finance, Accounting & Management Journal, 2025)
This research examines the role of Guest Relations Officers (GROs) in handling guest complaints at Zeus Restaurant, Apsara Beach Front Resort and Villa, Thailand, focusing on the effectiveness of various complaint management strategies and their impact on guest satisfaction. Using a qualitative research approach, the study involved semi-structured interviews with 10 GROs to explore the most common types of complaints, the resolution strategies implemented, and the outcomes of these strategies. Findings show that the main grievances relate to service delays, food quality, and staff behavior. GROs effectively addressed complaints through immediate acknowledgement, empathic communication, and prompt problem-solving. The research highlights the importance of follow-up, such as rechecking guest conditions and providing compensation, in improving guest satisfaction and loyalty. . The study emphasizes the importance of GRO training in emotional intelligence and problem-solving skills, and suggests the use of advanced technology and a structured complaint management system to maintain high service standards. This study contributes to the understanding of effective complaint handling practices in luxury hospitality environments and provides insights for the improvement of guest relations and operational excellence